Role of nuclear factor kappa- b (nf-kb) and its interactionWith hsamicrorna 146A in esophageal cancer - VIPUL CHAUDHARY,; PAMELA SINGH, (International Journal of Pharma and Bio Sciences, 2017)
Esophageal squamous cell carcinoma (ESCC) is one of the most common cancers in the world with extremely poor prognosis due to late presentation and rapid progression. SNPs (single nucleotide polymorphism) or mutations located within the miRNA regions has been shown to change the processing including binding affinity and specificity. miRNAs are acting as modulators or effectors of the NF-kB signalling pathway. The hereditary link of esophageal cancer is not very clear, there are several oncogenes such as EGFR, ERB2, MYC, CyclinD etc. and tumor suppressor genes e.g. TP53, P16, FHIT, RB, P14/ARF and telomerase have been shown to be involved in esophageal carcinogenesis.